2023
DOI: 10.1200/jco.2023.41.16_suppl.tps5633
|View full text |Cite
|
Sign up to set email alerts
|

The RAINBO MMRd-GREEN trial (GCIG/DGOG/ENGOT-EN142): A phase III trial on the addition of adjuvant durvalumab to radiotherapy in patients with high-risk MMRd endometrial cancer.

Abstract: TPS5633 Background: The molecular class of endometrial cancer (EC) is both prognostic and predictive in high-risk EC (HREC). The TransPORTEC research consortium showed that patients with MMRd HREC did not benefit from adjuvant chemotherapy added to radiotherapy. MMRd tumors are particularly sensitive to immunotherapy. We hypothesize that adjuvant durvalumab added to standard radiotherapy will increase recurrence-free survival (RFS) in patients with MMRd HREC. Methods: MMRd-GREEN is an international, open-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given efficacy in the advanced setting, studies are also investigating the primary end point is 3-year RFS. 70 However, radiation may also lead to immunosuppression, and results from studies of concurrent ICI and radiation in cervical and head and neck cancers have not shown a clinical benefit, calling into question mode and timing of radiation. [71][72][73] A subgroup analysis of GOG 258, a randomized study of chemotherapy (CT) or chemoradiotherapy (CRT) as adjuvant therapy in high-risk EC, found no benefit to the addition of radiation to chemotherapy in the MMR-D subgroup, 5-year RFS 52.5% (CRT) vs. 63.7% (CT) (HR, 1.34; 95% CI, 0.70-2.57).…”
Section: Clinical Trials Of Ici In Mmr-d/msi-h Ec: Adjuvant Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given efficacy in the advanced setting, studies are also investigating the primary end point is 3-year RFS. 70 However, radiation may also lead to immunosuppression, and results from studies of concurrent ICI and radiation in cervical and head and neck cancers have not shown a clinical benefit, calling into question mode and timing of radiation. [71][72][73] A subgroup analysis of GOG 258, a randomized study of chemotherapy (CT) or chemoradiotherapy (CRT) as adjuvant therapy in high-risk EC, found no benefit to the addition of radiation to chemotherapy in the MMR-D subgroup, 5-year RFS 52.5% (CRT) vs. 63.7% (CT) (HR, 1.34; 95% CI, 0.70-2.57).…”
Section: Clinical Trials Of Ici In Mmr-d/msi-h Ec: Adjuvant Settingmentioning
confidence: 99%
“…One arm of RAINBO, MMRd‐GREEN (NCT05255653), is a phase 3, randomized trial of adjuvant durvalumab for 1 year with standard radiotherapy compared to radiotherapy alone for stage IB/II and IIIA‐C MMR‐D EC. Accrual is ongoing, and the primary end point is 3‐year RFS 70 …”
Section: Clinical Trials Of Ici In Mmr‐d/msi‐h Ec: Adjuvant Settingmentioning
confidence: 99%